ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP DITINJAU DARI MOTIVASI BELAJAR - Ai Ira Listadewi, - (2020)
This study aims to analyze the presence or absence of differences in mathematical communication skills of junior high school students in terms of learning motivation and learning motivation dimensions. This research uses a quantitative approach with descriptive-comparative methods. The population in this study were all grade VIII students at SMP Kota Bandung odd semester 2020/2021 academic year. The sample in this study were 67 students. The research data obtained were student questionnaires and essay tests that were collected through google form media. The results of this study indicate: (1) There is a significant difference in the mathematical communication skills of junior high school students in terms of the level of learning motivation, namely the level of learning motivation is low and high; (2) There is no significant difference in mathematical communication skills of junior high school students in terms of the level of physiological needs; (3) There is no significant difference in mathematical communication skills of junior high school students in terms of the level of need for security; (4) There is no significant difference in mathematical communication skills of junior high school students in terms of the level of need for love; (5) There is a significant difference in the mathematical communication skills of junior high school students in terms of the level of need for appreciation, namely the level of need for appreciation is low to medium; (6) There is no significant difference in mathematics communication skills of junior high school students in terms of the level of self-actualization needs.